Effect of Temperature and Cuo-Nanoparticle Concentration on the Thermal Conductivity and Viscosity of an Organic Phase-Change Material - Galvez-Manriquez, D; Zapata-Ramirez, P; Vasco-Calle, D (Elsevier Ltd, 2018)
The main results of an experimental study of the effect of temperature and nanoparticle concentration on thermal conductivity and viscosity of a nanofluid are shown. The nanofluid was prepared with Octadecane, an alkane hydrocarbon with the chemical formula CH3(CH2)16CH3, as a base fluid and 75-nm CuO spherical nanoparticles. Since the base fluid is a phase change material (PCM) to be used in thermal storage applications, the engineered nanofluid is referred to as Nano-PCM. Three Nano-PCMs were prepared by the two-step method (2.5% w/v, 5.0% w/v, and 10.0% w/v). In order to increase the stability of the Nano-PCM, the surface of the CuO nanoparticles were modified with Sodium oleate, and it was verified by IR analysis. The modified CuO nanoparticles were dispersed with an ultrasonic horn. The thermal conductivity was measured with a thermal properties analyzer in the temperature range of 30–40 °C. The viscosity was measured in the temperature range of 30–55 °C. The results for the Nano-PCM showed that thermal conductivity is almost constant in the analyzed temperature range, and the viscosity decreases non-linearly with temperature. With respect to the effect of nanoparticle concentration, both thermal conductivity and viscosity increased with nanoparticle concentration. Thermal conductivity increased up to 9% with respect to the base fluid, and viscosity increased up to 60%, in both cases with increasing concentration. Finally, the viscosity measurements for different deformation rates (30–80 RPM) showed that the addition of nanoparticles modifies the rheological behavior of the base fluid, from a Newtonian to a shear thinning (power-law) non-Newtonian behavior. © 2017 Elsevier Ltd